Parameter of nonlinearity B/A of three-component systems with separate volumes of liquid, its vapor and a neutral gas - Perelomova, A. (Archives of Acoustics, 2005)
An expression of the excess entropy of a three-component mixture with separate volumes of liquid, vapor and neutral gas in terms of its excess pressure and density is obtained with accuracy up to quadratic nonlinear terms. The formulae of a small-signal sound speed and parameter of nonlinearity B/A defined by this expression depend on equilibrium mass concentrations of vapor and neutral gas and the initial pressure of the mixture. The only limitation is that the vapor and the inertial gas are ideal gases. Calculations of the sound velocity and the parameter of nonlinearity are presented for a mixture consisting of water and water vapor being in phase equilibrium and air.